Experimental model of pancreatitis in the dog - Pardo, Héctor A.; Servetti, Eduardo; Cartazzo, José M.; Noguera, Gustavo; Bonaba, Roberto (Cirugía del Uruguay, 1975)
The authors report a simple procedure to produce acute edematous pancreatitis experimentally, by injecting bile into the pancreatic duct, without ligating it, in a series of 10 dogs. The results were homogeneous from the clinical and pathological standpoints, as well as for the labora tory findings ( increase of the level of amylase both in blood and in the peritoneal exudate). The pressure at which the bile is injected must be measured and it must be from 9 to 10 cm of water. Provided this pressure is constant, the homogeneity of the results thus obtained make this procedure a proper experimental mcdel fer the assessment of different therapeutic procedures.